Painful scalp ulcers. - Cunha, Daniela; Freitas, Isabel; Neta, Jorge; Lamarão, Paulo; Cardoso, Jorge (Acta Médica Portuguesa, 2010)
Temporal arteritis is a systemic vasculitis mainly affecting large and medium sized vessels, temporal artery in particular. The authors report the case of a male who presented with large painful scalp ulcers over the temporo-parietal area, ipsilateral headache, amaurosis fugax and jaw claudication. Temporal arteries were thickened, painful and pulseless. Laboratory work revealed erythrocyte sedimentation rate of 63 mm and normochromic and normocytic anaemia. On histopathology transmural acute and chronic inflammation and multiple giant cells were patent in temporal artery wall. Ophthalmologic observation revealed significant visual impairment, mainly on the right eye. Regarding temporal arthritis diagnosis, prednisolone 1 mg/Kg/day was introduced. Clinical improvement was outstanding, although visual impairment remained. This case emphasizes early diagnosis and treatment importance in the avoidance of definitive sequela.